Perceptions of Indonesia State Civil Apparatus in supporting the Total Defense System before the Covid-19 Pandemic - Deni Dadang A.R; Haposan Simatupang; Asti Setya Wardani; Mhd Halkis (Technium Social Sciences Journal, 2021)
The involvement of the people in the total state defense system is very relevant to the current situation. In the atmosphere of the Covid-19 Pandemic, the ASN (Aparatur Sipil Negara/State Civil Apparatus) of the Indonesian Government as a group of civilian elites can provide an overview of how it perceives and supports the total defense system of the Indonesian state or in the defense concept it is called Sishankamra (Sistem Pertahanan dan Keamanan Rakyat Semesta/defense system and public security). This research used a quantitative approach before the Covid-19 Pandemic arrived in Indonesia. The results showed that individual factors determine people’s perceptions; therefore, the defense is more likely to be familiar. Even the individual desire to educate children from childhood is very dominant for that total support is a necessity.